Comparison of the Movement Disorder Society Parkinson's disease dementia criteria with neuropsychological testing. Issue 10 (13th May 2014) - Barton, Brandon R.; Bernard, Bryan; Czernecki, Virginie; Goldman, Jennifer G.; Stebbins, Glenn; Dubois, Bruno; Goetz, Christopher G.
Abstract The objective of our study was to compare Movement Disorder Society Task Force criteria for diagnosis of Parkinson's disease dementia (PDD) with the gold standard of traditional neuropsychological testing. A short checklist (Level I) and a protocol of neuropsychological tests (Level II) have been proposed by a Movement Disorder Society Task Force but not fully validated in clinical practice. Ninety‐one Parkinson's disease (PD) subjects were categorized as having dementia or no dementia based on a battery of neuropsychological test results and clinical judgment. The isolated components needed for Level I and Level II diagnoses were then culled from the neuropsychological evaluations and independently used to designate PDD. Compared with traditional neuropsychological testing, the sensitivity and specificity of Level I criteria for PDD was 66.7% and 98.8%, and for Level II criteria 100% and 92.7%, respectively. Using Level II criteria, 6 additional subjects were diagnosed with PDD that were classified as having no dementia when full neuropsychological data were used for the diagnosis. These 6 subjects had more education years and were less impaired on cognitive tests. The Movement Disorder Society's Level II criteria more frequently classify subjects with PDD than does traditional neuropsychological testing. Whereas Level II criteria may overclassify subjects as having PDD, they are very accurate in ruling out dementia. Movement Disorder Society's criteria are practical and timesaving, although full neuropsychological testing may still be needed. © 2014 International Parkinson and Movement Disorder Society